Determinan Factor On Behaviour Auditor Disfunction - Dirvi Abbas; Imam Hidayat (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research was conducted on Public Accountants in Indonesia. This study aims to investigate how Time Budget Pressure, Locus Of Control, Independence and Gender are related to Dysfunctional Behavior of Auditors in Indonesia Methodology/approach: Primary data collection method with questionnaire dissemination. Instrument trials use validity and reliability test methods. Test the data using model analysis, normality test, and model test. Test the hypothesis using SEM analysis. Findings: Based on the results of the study shows that there is a positive influence of Time Budget Pressure and Locus Of Control on the Auditor's Dysfunctional Behavior. However, there is no influence between independence and gender on the auditor's dysfunctional behavior. Practical implications: So that IAPI in audit training emphasizes more on case studies of timely completion of work, efficient allocation of audit time and evaluating appropriate audit evidence. Originality/value: There have been many studies in developed countries that discuss time budget pressure and locus of control for dysfunctional auditors, but there are still few studies in developing countries that discuss time budget pressure, locus of control, independence and gender on dysfunctional auditors.